Pendampingan Branding Product Tahu, Tempe, Toge dan Digital Marketing di Desa Gunung Kendang - Tri Susanti; Nanda S. Prawira; Onne Akbar Nur Ichsan (Lembaga Pengembangan Kinerja Dosen, 2023)
the purpose of this service is to provide knowledge about Product Branding and Marketing Digitalization of Tofu, Tempe Toge Products to the Gunung Kendang Community. So far, product packaging has not provided maximum hygiene and marketing, especially in the previous product packaging which still used plastic bags which were not good for health. So that assistance is needed for development in product packaging, and digitalization of marketing in an effort to increase the economy and product marketing. The methods for implementing the community partnership program service activities include; Methods of interviews, questionnaires, site condition surveys and area analysis, communication with the head of the RT Gunung Kendang and discussions with people who produce Toge, Tempe and Toge in identifying needs and supporting facilities in the production process, and determining digital marketing concepts. Through this mentoring activity produced several achievements, namely; Tofu, tempe and bean sprout business actors in Gunung Kendang Village can provide products with more attractive packaging designs, are more durable and more hygienic.